Buddhist (post) modernism in Robert Hass's early poetry and poetics: "The fullness of desire" - Stichl, Lutz (Peter Lang, 2025)
"This book is a first sustained scholarly effort to analyze reflections of Far Eastern, especially Buddhist-inspired aesthetics, culture, and philosophy in the poetry and criticism of Robert Hass. Three main concerns of his work can be accounted for by studying Hass's reception of Buddhist ideas. Firstly, poetic-ontological perspectives on the self and desire which are influenced by the concepts of annata (non-self) and tanha (craving). Secondly, appreciations of the sublime in the near-at-hand, i.e., a Buddhist understanding of interdependence. And lastly, Hass's negative capability in the face of philosophical discussions concerning the limits of language. These concerns manifest themselves in an idealistic understanding of the haiku and in a Buddhist-Romantic endeavor to contrive a more intimate relationship with nature. Additionally, it becomes evident in an ecopoetic desire to combat the abstractions and aberrations of modernity by means of Far Eastern aesthetics; as well as in a Buddhist-derived understanding of the paradox as a means of transcendence"--